Analyzing trends and suggested instructional strategies for Geometry education: Insights from Uganda Certificate of Education-Mathematics Examinations, 2016-2022 - Issa Ndungo; Edwin Akugizibwe; Sudi Balimuttajjo (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2024)
Geometry education plays a pivotal role in fostering analytical, spatial, and problem-solving skills among students. Nonetheless, there is still a problem with how well geometry training in Ugandan schools accomplishes these objectives and this is evident in the Uganda Certificate of Education (UCE) examinations. To close this gap, a comprehensive examination of data taken from Uganda National Examinations Board (UNEB) reports covering the years 2016 to 2022 was carried out; with an emphasis on candidates' performance, the study looks at common geometric ideas, pinpoints areas of weakness for candidates, and assesses response quality. This study's content analysis reveals notable variations in the quality of responses to various mathematics areas, with geometry consistently having the largest percentage of poor responses. Interestingly, in most areas, attempt levels positively correlate with response quality; but, in the case of geometry, this correlation reverses, suggesting that learners in this domain confront different problems. These problems include using geometric principles for problem-solving, combining algebraic and geometric concepts, and spatial visualization. The study advocates for using technology, active and problem-based learning; as these approaches provide opportunities for experiential learning, and conceptual knowledge reinforcement to learners.  All this will support ongoing attempts to enhance mathematics education, particularly in the field of geometry, within the Ugandan context.